Elbridge Gerry's salamander : the electoral consequences of the reapportionment revolution - Cox, Gary W.; Katz, Jonathan N. (Jonathan Neil), 1968- (Cambridge ; New York : Cambridge University Press, 2002)
The Supreme Court's reapportionment decisions, beginning with Baker v. Carr in 1962, had far more than jurisprudential consequences. They sparked a massive wave of extraordinary redistricting in the mid-1960s. Both state legislative and congressional districts were redrawn more comprehensively--by far--than at any previous time in our nation's history. Moreover, they changed what would legally happen should a state government fail to enact a new districting plan when one was legally required. This book provides the first detailed analysis of how judicial partisanship affected redistricting outcomes in the 1960s, arguing that the reapportionment revolution led indirectly to three fundamental changes in the nature of congressional elections: the abrupt eradication of a 6% pro-Republican bias in the translation of congressional votes into seats outside the south; the abrupt increase in the apparent advantage of incumbents; and the abrupt alteration of the two parties' success in congressional recruitment and elections.
pt. I. Introduction. 1. Introduction. 2. The Reapportionment Revolution -- pt. II. Democrats and Republicans. 3. A Model of Congressional Redistricting in the United States. 4. The Case of the Disappearing Bias. 5. The Role of the Courts in the 1960s Redistricting Process. 6. Bias, Responsiveness, and the Courts. 7. Redistricting's Differing Impact on Democratic and Republican Incumbents -- pt. III. Incumbents and Challengers. 8. The Growth of the Incumbency Advantage. 9. Candidate Entry Decisions and the Incumbency Advantage. 10. Redistricting and Electoral Coordination. 11. Redistricting, the Probability of Securing a Majority, and Entry. 12. Reassessing the Incumbency Advantage -- pt. IV. Conclusion. 13. Final Thoughts.
Includes bibliographical references (pages 219-227) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Apportionment (Election law) -- United States; Election districts -- United States; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-; Répartition des sièges -- États-Unis.; Circonscriptions électorales -- États-Unis.; États-Unis -- Politique et gouvernement -- 1945-1989.; États-Unis -- Politique et gouvernement -- 1989-; POLITICAL SCIENCE -- Government -- Legislative Branch; Apportionment (Election law); Election districts; Politics and government; United States; Wahlkreiseinteilung; Wahlverfahren; USA; Répartition des sièges -- Etats-Unis.; Circonscriptions électorales -- Etats-Unis -- 1945-.; États-Unis -- Politique et gouvernement -- 1945-1990.; États-Unis -- Politique et gouvernement -- 1990- ...; Since 1945; Electronic books; Electronic books